2019
DOI: 10.1051/e3sconf/201912506002
|View full text |Cite
|
Sign up to set email alerts
|

Does Economic Growth Reduce Pollution? Empirical Evidence from Low Income Countries

Abstract: The issue of environmental degradation has long been associated as a residue of the economic development process, especially in low income countries. Development activities have to continue nevertheless, because people's welfare is the goal. This study aims to find the impact of economic growth, population and energy consumption to environmental pollution. Another purpose is to prove the Environmental Kuznets Curve (EKC) hypothesis. The methods utilized is panel data regression with fixed effect model using Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
4
1
2
Order By: Relevance
“…This result indicates that the EKC hypothesis 3 asserting that there is an inverted Ushaped relationship between environmental pollution and GDP per capita (economic growth) is valid for developing countries. This finding is consistent with the results reported by Saboori et al (2012), Yavuz (2014), Hanif et al (2019), andRofiuddin et al (2019). Additionally, the rise in CO2 emissions accompanying economic growth can be explained by the intense use of non-renewable energy sources in the production process, as the average share of NREC in the total energy consumption in these countries for the period between 1990 and 2014 was 60%.…”
Section: Results Of Two-step Difference Gmm Estimationsupporting
confidence: 91%
See 1 more Smart Citation
“…This result indicates that the EKC hypothesis 3 asserting that there is an inverted Ushaped relationship between environmental pollution and GDP per capita (economic growth) is valid for developing countries. This finding is consistent with the results reported by Saboori et al (2012), Yavuz (2014), Hanif et al (2019), andRofiuddin et al (2019). Additionally, the rise in CO2 emissions accompanying economic growth can be explained by the intense use of non-renewable energy sources in the production process, as the average share of NREC in the total energy consumption in these countries for the period between 1990 and 2014 was 60%.…”
Section: Results Of Two-step Difference Gmm Estimationsupporting
confidence: 91%
“…The researchers found that the causality between economic growth and carbon emissions varied among the studied countries; there was bidirectional causality in China, India, Canada, Italy, Japan, and the USA, whereas there was unidirectional causality in France and no causality in Germany and the UK. According to the results obtained from the estimations of fixed effects model by using the annual data of 11 low-income countries for the period between 1991 and 2014, Rofiuddin et al (2019) determined that economic growth increased the environmental pollution and they achieved empirical results suggesting the validity of EKC hypothesis in these countries. Hanif et al (2019) carried out a study on 15 developing Asian countries by using a panel ARDL bound test and determined that economic growth increased CO2 emissions.…”
Section: How Does Economic Growth Affect Co2 Emissions?mentioning
confidence: 99%
“…Metode yang dipakai dalam penelitian ini merupakan metode analisis data panel. Metode analisis data panel merupakan gambungan antara deret waktu (time series) dengan analisis deret wilayah (cross Section) (Iskandar et al, 2019;Mohammad & Firmansyah, 2018;Rofiuddin et al, 2019) Terdapa bentuk regresi untuk data panel di dalam penelitian ini adalah sebagai berikut : = 0 + 1 + 2 + 3 + TK merupakan kemiskinan, PDRB merupakan Produk domestik regional bruto, IPM singkatan Indeks Pembangunan Manusia, Zakat Ada Beberapa keuntungan yang akan kita dapatkan didalam menggunakan data panel. Menurut Widarjono (2013) keuntungan -keuntungan yang diperoleh diantaranya adalah data panel merupakan gabungan dua data time series dan cross section mampu untuk menyediakan data lebih banyak sehingga akan menghasilkan degree of freedom yang lebih besar.…”
Section: Metode Penelitianunclassified
“…The results of other studies show different results. The negative impact of economic activity causes water pollution, air pollution, and others [18][19][20].…”
Section: Introductionmentioning
confidence: 99%